﻿An analysis of patient’s and disease related factors predictive of the outcomes of surgery for carpal tunnel syndrome - Zyluk, Andrzej; Zyluk-Gadowska, Paulina; Kolodziej, Lukasz; Szlosser, Zbigniew (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Purpose Outcomes of surgery for carpal tunnel syndrome may differ in relation to certain factors like age, duration of symptoms, clinical and electrophysiological severity. The objective of this study was an investigation into the hypothesis that several factors are predictive of results of surgical treatment of the condition.Methods The pre- and postoperative records of 1,117 patients: 909 women (81 %) and 208 men (19 %) with a mean age of 63 years were analysed. Outcomes recorded in the sensory and functional severity scores of the Levine questionnaire were dichotomized into achieving or not-achieving a minimally clinically important difference. The effect of selected variables: sex, age, duration of symptoms, clinical and electrophysiological severity of and presence of comorbidities on outcomes of surgery at 6 months was investigated.Results Univariate and multivariate analysis of covariates based on sex, age, duration of the disease and its clinical severity showed female gender and worse baseline symptom severity scores to be significant predictors for an improvement following carpal tunnel syndrome surgery. It showed also younger age, shorter duration of symptoms and higher baseline symptom severity scores to be predictive of a greater improvement of total grip strength, and younger age to be predictive of a greater pain cessation following surgery.Conclusion Of all considered patient’s and disease related factors, the baseline clinical severity expressed in the Levine symptom severity scores had appeared to be the strongest predictor of better outcomes of surgery for carpal tunnel syndrome.
Keywords: Karpaltunnelsyndrom; Pathologie; Vorhersageparameter für das Ergebnis